Efecto de cuatro dosis de gallinaza en los componentes agronómicos y rendimiento de Brassica olerácea L., var. capitata, col roja, en Zungarococha - Loreto, 2022 - Garcia Torres, Fernando Alonso (2023)
The experimentation "Effect of four doses of gallinaza on the agronomic components and yield of Brassica olerácea l. , var. capitata, Red cabbage, in Zungarococha-Loreto.2022 "was forged on the grounds of the Faculty of Agronomy, of the UNAP, located near the town center of Zungarococha-Iquitos, having had as its primary objective to evaluate the effects of the doses of chicken, in the agronomic components and yield of Brassica olerácea L, var.capitata, Red cabbage. The experimental sketch was that of Completely Random Blocks, whose results were analyzed and discussed through the Analysis of Variance, and Tukey's comparison test. With the results obtained, the following conclusions were reached: The increase in the dose of chicken transcends the characteristics and yield of the crop. The results of the characteristics and yield of the crop increased as the dose of chicken was increased The T4 (40 t of chicken / ha), presented the best results of the characteristics and yield of the crop. The weight of heads/ha obtained in T4 with 40 t of chicken/ha (2,900 Kg/ha) are below the national average.